2019
DOI: 10.1016/j.heliyon.2019.e01783
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency due to bilateral adrenal metastases – A systematic review and meta-analysis

Abstract: Objective Bilateral adrenal metastases may cause adrenal insufficiency (AI) but it is unclear if screening for AI in patients with bilateral adrenal metastases is justified, despite the potential for adrenal crises. Method A search using PubMed/Medline, ScienceDirect and Cochrane Reviews was performed to collect all original research articles and all case reports from the past 50 years that describe AI in bilateral adrenal metastases. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
0
35
2
1
Order By: Relevance
“…The prevalence of adrenal insufficiency in bilateral adrenal metastasis is approximately 8%, which was calculated using strict inclusion criteria of documented bilateral disease and ACTH stimulation test for diagnosis (17). Secondary outcomes also demonstrated that 15% (3/20) of the cases were caused by breast cancer (17). Adrenal insufficiency should be considered as it may be the solitary sign of disease, as demonstrated in our patient.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The prevalence of adrenal insufficiency in bilateral adrenal metastasis is approximately 8%, which was calculated using strict inclusion criteria of documented bilateral disease and ACTH stimulation test for diagnosis (17). Secondary outcomes also demonstrated that 15% (3/20) of the cases were caused by breast cancer (17). Adrenal insufficiency should be considered as it may be the solitary sign of disease, as demonstrated in our patient.…”
Section: Discussionmentioning
confidence: 69%
“…A high index of suspicion is paramount in patients with a prior history of cancer presenting with hypotension, fatigue, nausea, vomiting, weakness, particularly in the setting of hyponatremia and normal to high potassium levels. The prevalence of adrenal insufficiency in bilateral adrenal metastasis is approximately 8%, which was calculated using strict inclusion criteria of documented bilateral disease and ACTH stimulation test for diagnosis (17). Secondary outcomes also demonstrated that 15% (3/20) of the cases were caused by breast cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…The possible tumor-reducing effect of replacement therapy in one of our cases confused and delayed the diagnostics. Glucocorticoids are part of the standard regimen for several lymphoid cancers, due to steroid sensitivity of tumor cells that seems to be more pronounced for immature lymphoid cells (4). Glucocorticoids have direct actions on gene transcription through glucocorticoid response elements (GREs) and indirect actions through interaction with transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…While LAC rarely metastasizes to unusual locations, they most commonly do to the liver, adrenal glands and bones (3). Between 28 to 42% of LAC and approximately 30% of breast cancers metastasize to the adrenals (4). Adrenal insufficiency (AI), occurs in approximately 3 to 8% of individuals with bilateral adrenal metastases (5).…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal insufficiency (AI), occurs in approximately 3 to 8% of individuals with bilateral adrenal metastases (5). AI was most commonly seen in bilateral adrenal metastases from LC (4).…”
Section: Introductionmentioning
confidence: 99%